Wonder, Education, and Human Flourishing Theoretical, Empirical, and Practical Perspectives - Schinkel, Anders (VU University Press, 2020)
The premise that underlies this volume is that there are strong interconnections between wonder, education and human flourishing. And more specifically, that wonder can make a significant difference to how well one's education progresses and how well one's life goes. The contributors to this volume - both senior, well-known and beginning researchers and students of wonder - variously explore aspects of these connections from philosophical, empirical, theoretical and practical perspectives. The three chapters that comprise Part I of the book are devoted to the importance of wonder for education and for human flourishing. Part II contains four chapters offering conceptual analyses of wonder and perspectives from developmental psychology and philosophy (Spinoza, Wittgenstein, philosophy of religion). The seven chapters that form Part III contain a wealth of ideas and educational strategies to promote wonder in education and teacher education. This volume not only underlines and articulates the importance of wonder in education and in life but also offers fresh perspectives, allowing us to look with renewed wonder at wonder itself.